Australian catholic teachers’ preparedness in identifying and responding to harmful sexual behavior and their training and resource needs - Lesley-anne Ey; Neil Tippett; Elspeth McInnes; Lewis Cockram; Anissa Ostovar-Ravare (Child Protection and Practice)
Background: Schools are often at the forefront of needing to identify and respond to harmful sexual behavior (HSB). However, there is limited understanding about what training and resources Australian teachers receive on HSB or what they need. Objective: To explore Catholic Education staff's preparedness and their training and resource needs for identifying and responding to HSB in education settings. Participants: and Setting: Seventy-four Catholic education staff answered an online survey, and a further 14 Catholic education pastoral care and leadership staff engaged in single. Method: Online survey and single interviews. Findings: Overall, participants felt most prepared to identify HSB and provide an immediate response to HSB, while they felt least prepared to respond to the parental community and to the families of children affected by HSB. Notably, teachers felt the least prepared to provide ongoing support to children affected by HSB and to respond to families and the parental community in matters concerning HSB. Participants called for training and resources to better support education staff in identifying and responding to HSB. Conclusion: This research has demonstrated that Catholic Education staff feel better prepared in identifying and responding to several elements of HSB than previous research with teachers has indicated, however they still feel inadequate in ongoing responses to children affected by HSB and in responding to parents.